2016
DOI: 10.32890/mjli2016.13.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Lesson Study as an Innovative Professional Development Model Among Malaysian School Teachers

Abstract: Purpose-This qualitative study explored the implementation of Lesson Study, a kind of teacher-directed and bottom-up approach of the Japanese model of teacher professional development in the Malaysian education context. It seeks to answer the question of how implementation of lesson study as an innovative professional development model among Malaysian school teachers influences teachers' pedagogical content knowledge, and what school-based factors support or hinder the implementation of lesson study in the Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
1
11
0
2
Order By: Relevance
“…Regarding the first research question, the results showed that most of the teachers agreed on the idea that LS was influential in encouraging teachers' exchange activities which might create the best opportunities for them to share ideas and receive constructive feedback from their fellow teachers contributing to developing their CPD (Mon et al, 2016;Matoba et al, 2007). A possible explanation for this finding could be that LS requires teachers' collaborative participation in sharing activities with their fellow teachers so as to reach a consensus for the improvement of instructional practices (Wood & Cajkler, 2018;Marble, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the first research question, the results showed that most of the teachers agreed on the idea that LS was influential in encouraging teachers' exchange activities which might create the best opportunities for them to share ideas and receive constructive feedback from their fellow teachers contributing to developing their CPD (Mon et al, 2016;Matoba et al, 2007). A possible explanation for this finding could be that LS requires teachers' collaborative participation in sharing activities with their fellow teachers so as to reach a consensus for the improvement of instructional practices (Wood & Cajkler, 2018;Marble, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be explained by the fact that LS creates favorable conditions for the teachers to plan teaching strategies and logically conduct the lesson through its different steps (e.g., collaboratively planning, discussing the lesson, etc.) (Mon et al, 2016;Stepanek et al, 2007). By doing this, it ensures that all the teachers in the group could be better equipped with sufficient knowledge of content, student agents, instruction, and so on, serving back to their CPD as well as satisfying the need for student learning (Matoba et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the advantages of this method include a significant motivational influence (interest, satisfaction, independence, confidence in one՚s own abilities), the formation of the physical education teacher՚s awareness of his own role and importance in the team, understanding of the specifics of the activity of the physical education department or its individual elements, etc. As for rotation [13], this is a method of non-formal learning, which involves familiarizing the employee of the physical education department with various activities of the structural unit, cooperation with other units, as well as direct participation in the performance of relevant tasks.…”
Section: форми організації та методи професійного розвитку викладачів...mentioning
confidence: 99%
“…In addition, as claimed by Yoshida (2002), being the primary form of professional development in different parts of the world now (e.g. Clivaz, 2016;Mon et al, 2016;N ı Sh uilleabh ain, 2015;Vermunt et al, 2019), LS has provided teachers with the opportunities to examine diverse factors that frame the teaching and learning processes. One of the recurrent themes being continuously discussed by teachers and scholars in LS is bansho.…”
Section: Bansho and Lesson Studymentioning
confidence: 99%